SISTEM INFORMASI DATA TRANSAKSI ICE CREAM WALLS PADA STOCK POINT (STP) PLUS - Asrin, Elzas (FORTECH (Journal of Information Technology), 2020)
Currently transaction Ice Cream Walls In Stock Point (STP) Plus Sungai Bahar is still done manually so that the data generated is less than optimal is less effective in searching for information on the data that you want to find, lack of accurate data is processed, and also the need for cost will be issued to obtain a report. For that we need to implement an information system design with Visual Basic 6.0 application, the data processing transactions on the Walls Ice Cream Stock Point (STP) Plus Sungai Bahar. With the new system is expected to overcome the constraints that exist on the old system.